The mediating role of opportunity recognition between education, experience and venture creation by women entrepreneurs in India - Choudhary, Jyoti; Hashim, Haslinda; Ho, Jo Ann; Sambasivan, Murali (Human Resource Management Academic Research Society, 2020)
Venture creation by both, men and women are essential for economic development. However, studies suggest that gender gap in SMEs in India is highest in the world. Empirical evidence suggest that opportunity recognition is the core of venture creation. While past studies have advanced knowledge on dimensions of individual factors and identified education and experience affecting opportunity recognition, surprisingly, little knowledge have been advanced on the mediating role of opportunity recognition in education, experience and venture creation in context of women entrepreneurs in SME sector in India. The purpose of this article is therefore to propose a conceptual model integrating education, experience, opportunity recognition and venture creation. Based on the synthesis of vast amount of prior literature, a conceptual model of venture creation is developed to explain the relationships amongst the constructs under study. Consequently, testable propositions are proposed for future empirical examinations.